Living with the state: The incomes and work incentives of tenants in the social rented sector - Christopher Giles; Paul Johnson; Julian McCrae; Jayne Taylor (Institute for Fiscal Studies (IFS), 1996)
This report analyses the changing economic positions of tenants in subsidised public housing. It shows how low their incomes are today, how these low incomes interact with higher rents and the housing benefit system to reduce their returns to work and looks at a number of reforms to the benefit system.
Keywords: 330